SIG/USE Research Symposium: Making Research Matter: Connecting Theory and Practice. Issue 3 (February 2016) - Willson, Rebekah; Greyson, Devon; Burnett, Gary; Given, Lisa
Abstract : EDITOR'S SUMMARY Special Interest Group/Information Needs, Seeking and Use (SIG/USE) convened at the 2015 ASIS&T Annual Meeting to explore the links between theory and practice in information behavior. In his keynote address, Ross Todd urged the audience to go beyond models and aim for synthesis and meta‐analysis, focusing on the user. Lightning talks addressed a social cognitive theory analysis of a program for disadvantaged youth; adults with limited literacy and health information; mobile information workers; forming a community of practice; and information sharing practices among online communities. A key takeaway was that research should actively involve communities and their members rather than simply being about them. Safiya Noble's keynote highlighted hidden biases in automated search engine returns with encouragement to design algorithms enabling users to opt in or out of filtered returns. Attendees explored the topics raised further during a mixer chat and table talks. The symposium ended with presentations for the best paper, poster and research proposal and awards for student and international conference travel.